2003
DOI: 10.2337/diacare.26.10.2923
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Coronary Artery Calcification in Type 1 Diabetes

Abstract: OBJECTIVE—Coronary artery disease (CAD) occurs earlier in life and is more often fatal in people with type 1 diabetes. This excess risk seems to be higher than in those with type 2 diabetes and is poorly explained by conventional risk factors. The role of glycemic control is controversial and has not been previously addressed in a prospective manner using a reliable marker for subclinical CAD, such as coronary artery calcification (CAC), measured by electron beam computed tomography (EBCT). RESE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
2
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 34 publications
5
87
2
4
Order By: Relevance
“…Two studies (18,19) failed to demonstrate a relationship between glycemia and CAC in type 1 diabetes, whereas one did (20). These studies showed relationships with traditional CVD risk factors, but a smaller sex difference in CAC than is usual for the nondiabetic population, consistent with the reduction in the difference between sexes for CAD in type 1 diabetes.…”
supporting
confidence: 48%
“…Two studies (18,19) failed to demonstrate a relationship between glycemia and CAC in type 1 diabetes, whereas one did (20). These studies showed relationships with traditional CVD risk factors, but a smaller sex difference in CAC than is usual for the nondiabetic population, consistent with the reduction in the difference between sexes for CAD in type 1 diabetes.…”
supporting
confidence: 48%
“…In view of the increasing perception of the serious cardiovascular risk already present in young T1DM patients (32) and 460 of its rapid progression in young adults (33), early intervention should target the modifiable risk factors in genetically predisposed individuals (with a positive family history of atherosclerosis). Although metabolic control remains the primordial therapeutic target in these patients, it does not explain the total coronary artery disease risk in T1DM (34).…”
Section: Endothelium and Sod In Diabetic Childrenmentioning
confidence: 99%
“…5 Although CAC is associated with measures of obesity obtained at the same time as the CAC measurement, 6 only one study has investigated the association between obesity and progression of CAC, and that study included only those with type I diabetes. 7 Thus, little is known about the role of obesity in the progression of CAC in asymptomatic individuals free of diabetes.…”
mentioning
confidence: 99%